1996
DOI: 10.1074/jbc.271.20.11627
|View full text |Cite
|
Sign up to set email alerts
|

Individual Leaflets of a Membrane Bilayer Can Independently Regulate Permeability

Abstract: Water rapidly crosses most membranes, but only slowly crosses apical membranes of barrier epithelia such as bladder and kidney collecting duct, a feature essential to barrier function. How apical membrane structure reduces permeabilities remains unclear. Cell plasma membranes contain two leaflets of distinct lipid composition; the role of this bilayer asymmetry in membrane permeability is unclear. To determine how asymmetry of leaflet composition affects membrane permeability, effects on bilayer permeation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 26 publications
5
59
0
Order By: Relevance
“…Before flux measurements, extravesicular CF was removed by passing the liposomes through a Sephadex G-50 column as described previously (11). Previous studies have demonstrated that this approach forms unilamellar vesicles (5,12); median vesicular size was determined by quasielastic light scattering (5,11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before flux measurements, extravesicular CF was removed by passing the liposomes through a Sephadex G-50 column as described previously (11). Previous studies have demonstrated that this approach forms unilamellar vesicles (5,12); median vesicular size was determined by quasielastic light scattering (5,11).…”
Section: Methodsmentioning
confidence: 99%
“…Vesicles were prepared by heating to 40°C and then cooling on ice three times, followed by 20 serial extrusions of the mixture through a 0.1-m pore polycarbonate filter using an Avanti mini-extruder (Avanti Polar Lipids, Inc., Alabaster, AL) warmed on a heating block to ϳ50°C as described (5,10,11). Before flux measurements, extravesicular CF was removed by passing the liposomes through a Sephadex G-50 column as described previously (11). Previous studies have demonstrated that this approach forms unilamellar vesicles (5,12); median vesicular size was determined by quasielastic light scattering (5,11).…”
Section: Methodsmentioning
confidence: 99%
“…Water Permeability Measurements-Osmotic water permeability (P f ) was measured at 25 C as described (3,18,20). All other permeabilities were measured at 25 C also.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments revealed an extremely low water permeability for exofacial liposomes of 2.4 Ϯ 0.4 ϫ 10 Ϫ4 cm/s, whereas cytoplasmic liposomes were 18.1 times more permeable with a P f ϭ 4.4 Ϯ 0.3 ϫ 10 Ϫ3 cm/s (p Ͻ 0.05). Previous work from our laboratory has shown that the leaflets in a bilayer each offer independent resistances to water and solute permeation (18,19). From Equation 1 we can calculate a single leaflet permeability from the exofacial liposomes and a single leaflet permeability for the cytoplasmic liposomes (both symmetric bilayers) and combine them to arrive at a theoretical permeability for an MDCK apical membrane.…”
Section: Mdck Apicalmentioning
confidence: 99%
See 1 more Smart Citation